Precision diagnosis of maturity-onset diabetes of the young with next-generation sequencing: Findings from the MODY-IST study in adult patients - ARĞA, KAZIM YALÇIN (My University, 2022)
Maturity-onset diabetes of the young (MODY) is a highly heterogeneous group of monogenic and nonautoimmune diseases. Misdiagnosis of MODY is a widespread problem and about 5% of patients with type 2 diabetes mellitus and nearly 10% with type 1 diabetes mellitus may actually have MODY. Using next-generation DNA sequencing (NGS) to facilitate accurate diagnosis of MODY, this study investigated mutations in 13 MODY genes (HNF4A, GCK, HNF1A, PDX1, HNF1B, NEUROD1, KLF11, CEL, PAX4, INS, BLK, ABCC8, and KCNJ11). In addition, we comprehensively investigated the clinical phenotypic effects of the genetic variations identified. Fifty-one adult patients with suspected MODY and 64 healthy controls participated in the study. We identified 7 novel and 10 known missense mutations localized in PDX1, HNF1B, KLF11, CEL, BLK, and ABCC8 genes in 29.4% of the patient sample. Importantly, we report several mutations that were classified as \"deleterious\" as well as those predicted as \"benign.\" Notably, the ABCC8 p.R1103Q, ABCC8 p.V421I, CEL I336T, CEL p.N493H, BLK p.L503P, HNF1B p.S362P, and PDX1 p.E69A mutations were identified for the first time as causative variants for MODY. More aggressive clinical features were observed in three patients with double- and triple-heterozygosity of PDX1-KLF11 (p.E69A/p.S182R), CEL-ABCC8-KCNJ11 (p.I336, p.G157R/p.R1103Q/p.A157A), and HNF1B-KLF11 (p.S362P/p.P261L). Interestingly, the clinical effects of the BLK mutations appear to be exacerbated in the presence of obesity. In conclusion, NGS analyses of the adult patients with suspected MODY appear to be informative in a clinical context. These findings warrant further clinical diagnostic research and development in different world populations suffering from diabetes with genetic underpinnings.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Temel Bilimler; Medicine; Health Sciences; Internal Medicine Sciences; Medical Genetics; Life Sciences; Biotechnology; Molecular Biology and Genetics; Natural Sciences; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Mikrobiyoloji; Yaşam Bilimleri (LIFE); GENETİK VE KALITIM; Moleküler Biyoloji ve Genetik; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; MICROBIOLOGY; Life Sciences (LIFE); GENETICS & HEREDITY; MOLECULAR BIOLOGY & GENETICS; Genetics; Molecular Biology; Applied Microbiology and Biotechnology; Molecular Medicine; Genetics (clinical); diabetes; MODY; next-generation sequencing; genetic variation; diagnostics; HEPATOCYTE NUCLEAR FACTOR-1-ALPHA; GENE-MUTATIONS; CLINICAL-FEATURES; MISSENSE MUTATION; TURKISH CHILDREN; COMMON-CAUSE; GCK GENE; TYPE-2; MELLITUS; IDENTIFICATION